2019
DOI: 10.1002/cbdv.201900366
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Aspects of Garcinol and Isogarcinol: Recent Developments

Abstract: The natural polyisoprenylated benzophenone derivatives garcinol and isogarcinol are secondary plant metabolites isolated from various Garcinia species including Garcinia indica. This review takes stock of the recent chemical and biological research into these interesting natural compounds over the last five years. New biological sources and chemical syntheses are discussed followed by new insights into the activity of garcinol and isogarcinol against cancer, pathogenic bacteria, parasite infections and various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 86 publications
(251 reference statements)
0
28
0
Order By: Relevance
“…Chemically, garcinol is polyisoprenylated benzophenone (Figure 1) mainly found in Garcinia indica (Kokum) and Garcinia cambogia (Malabar tamarind) of the Mangosteen and Clusiaceae families, respectively [22]. Methanol extraction of dried G. indica plums resulted in the promising extraction of garcinol [9]. Further, re-dissolution of the above prepared extract in ethyl acetate followed column chromatography on silica gel.…”
Section: Chemistry Of Garcinolmentioning
confidence: 99%
See 3 more Smart Citations
“…Chemically, garcinol is polyisoprenylated benzophenone (Figure 1) mainly found in Garcinia indica (Kokum) and Garcinia cambogia (Malabar tamarind) of the Mangosteen and Clusiaceae families, respectively [22]. Methanol extraction of dried G. indica plums resulted in the promising extraction of garcinol [9]. Further, re-dissolution of the above prepared extract in ethyl acetate followed column chromatography on silica gel.…”
Section: Chemistry Of Garcinolmentioning
confidence: 99%
“…Further, re-dissolution of the above prepared extract in ethyl acetate followed column chromatography on silica gel. From hexane elute, yellow needle-like crystals of garcinol with a melting point of 132 • C have been reported [9,23]. Another method comprises the initial removal of hydroxycitric acid from plant fruits.…”
Section: Chemistry Of Garcinolmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracts of the pericarp, epicarp, and seeds of Garcinia have demonstrated antioxidant, anti-inflammatory, leishmanicidal, and antiprotozoal activities [ 21 , 22 , 23 ]. Another study also reported the presence of the bioflavonoids volkensiflavone, fukugetin [ 24 ], and prenylated xanthones [ 25 ]. These compounds have been associated with biological activities such as free-radical scavenging, antiulcer effects [ 26 ], cytotoxicity, inhibition of nitric oxide synthase [ 27 ], chemoprevention of cancer [ 28 ], induction of apoptosis [ 29 ], anti-HIV [ 30 ], and trypanocidal effects [ 31 ].…”
Section: Introductionmentioning
confidence: 99%